Análise de rigidez e danificação de misturas asfálticas recicladas a quente com diferentes tipos e teores de RAP - Correa, Bethania Machado (2020)
The constant search for sustainable alternatives intending to reduce the environmental impact gave research visibility for the developed subject. In this context, the paving milled material, known as RAP (Reclaimed Asphalt Pavement), emerged as a study object for researches. In order to provide its reuse, they seek to deepen the material behavior knowledge when incorporated into new asphalt mixtures. Thus, this work aims to study the mechanical behavior of recycled mixtures with different sources of RAP and incorporation levels. To achieve the proposed objective, eight mixtures were compound, divided into two large groups: four mixtures containing 50/70 virgin binder and RAP from a source 1; four mixtures containing virgin binder 60/85 and RAP from source 2, following Marshall Dosage methodology. For each of this groups, the RAP incorporation levels were 0%, 10%, 20% and 30%. The virgin aggregate used was a granitic type, from a quarry from the city of Eldorado do Sul - RS. Source 1 of RAP contains 50/70 neat binder in its composition and source 2 of RAP contains 60/85 polymer modified binder. From previous results, the design bitumen contents found confirmed a reduction in the added virgin binder, indicating that a portion of the RAP binder was reactivated. At the laboratory, resilience module (MR) and dynamic module (MD) tests were performed for stiffness evaluation. Moreover, moisture-induced damage (DUI); uniaxial repeated load (flow number); tensile strength by diametrical compression (RT) and tensile-compression fatigue were also conducted. The MR results indicated that, for 50/70 mixtures, the increase in binder content decreased the stiffness, being more important than the inserted RAP content. Whereas for the 60/85 mixtures, the insertion of RAP increased the stiffness. Dynamic Module results corroborated with the previous analysis, the highest values of stiffness found were for mixtures with binder 50/70. In 60/85 scenario, the addition of 30% RAP in mixtures increased the stiffness. DUI results showed that water did not damaged any of analyzed mixtures. For the FN and RT tests, the addition of RAP increased the values results for both types of binder. In the fatigue analysis, mixtures with 60/85 binder presented better performance than 50/70, and the addition of RAP slightly decreased the performance. However, using the cracked area shift function, the mixtures containing 60/85 binder with addition of 10% and 20% of RAP showed almost zero damage. Finally, this research has shown that the final binder content of the mixtures and the type of virgin binder added are also factors that directly influence recycled mixtures performance. Mixtures with the addition of RAP can behave similarly, or even better, than virgin mixtures, making viable sustainable future projects that use this material in layers of asphalt coatings.